EMODIN DOWNREGULATES CELL PROLIFERATION MARKERS DURING DMBA INDUCED ORAL CARCINOGENESIS IN GOLDEN SYRIAN HAMSTERS - Manimaran, Asokan; Buddhan, Rajamanickam; Manoharan, Shanmugam (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Cell-cycle disruption is the major characteristic features of neoplastic transformation and the status of cell-cycle regulators can thus be utilized to assess the prognostic significance in patients with cancer. The PCNA, cyclin D1, CDK4, CDK6 and survivin expression in the buccal mucosa was utilized to evaluate the Emodin efficacy on abnormal cell proliferation during 7,12-dimethylbenz(a)anthracene (DMBA) induced oral carcinogenesis in golden Syrian hamsters. Materials and methods: Topical application of DMBA, three times a week for 14 weeks, on the hamsters’ buccal pouches developed well differentiated squamous cell carcinoma. Results: Cyclin D1 and PCNA over-expression and up-regulation of CDK4, CDK6 and survivin were noticed in the buccal mucosa of hamsters treated with DMBA alone. Emodin administration (50mg/kg b.w) orally to hamsters treated with DMBA down-regulated the expression of cell proliferation markers in the buccal mucosa. Conclusions: The anti-cell proliferative role of Emodin is owing to its modulating efficacy on cell-cycle markers towards the tumor suppression during DMBA induced oral carcinogenesis.